'MEETING OF WATERS'? THE COMPLEX LANDSCAPE OF THE POLISH RIGHT TO THE CITY ACTIVISM - PLUCIŃSKI, PRZEMYSŁAW (Society Register, 2020)
For over a decade, the explosion of various forms of urban activism has been observed: so- called urban social movements or the right to the city (RTTC) movements actively participate in the realm of non-institutional politics. This trend has been observed both world-wide and in Europe, particularly in the countries of Central and Eastern Europe. Poland is also a clear example of this tendency. The paper presented aims to achieve two goals. First of all, it is based on desk research and offers a broad literature overview, indicating the main directions and results in urban activism research in Poland of the last 10 years. Recalling and discussing the broadest possible body of literature, with particular emphasis on Polish-language references, should be useful for international readers and researchers. Secondly, the paper attempts to synthesize these current research results, including the authors own research results, identifying the complexity of the field of urban activism. As a result, it points to various entities using the RTTC slogan in their social struggles, consequently identifying two main types of RTTC activism: radical and middle-class (petite bourgeoisie?) movements.